2012
DOI: 10.3109/00365599.2012.702786
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and bother of postmicturition dribble in Finnish men aged 30–80 years: Tampere Ageing Male Urologic Study (TAMUS)

Abstract: The prevalence of the postmicturition dribble was found to be high in this survey. Half of the 30-year-old men and two-thirds of the men aged 60-80 years had postmicturition dribble. Dribbling into trousers increased with age but as a severe symptom, it was rare (0.5%). Minor problems from postmicturition dribble were common, but major bother occurred seldom (1.1%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Contrary to traditional assumptions [3][4][5][6], recent evidence suggests that PMD prevalence in men may be higher than previously expected. Some studies report PMD prevalence of > 50% [8][9][10]. Recent studies also suggest that PMD may be one of the most bothersome LUTS in men [8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to traditional assumptions [3][4][5][6], recent evidence suggests that PMD prevalence in men may be higher than previously expected. Some studies report PMD prevalence of > 50% [8][9][10]. Recent studies also suggest that PMD may be one of the most bothersome LUTS in men [8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers' indifference to postmicturition symptoms may be due to the belief that postmicturition symptoms might have a lower prevalence and elicit less discomfort than storage and voiding symptoms do [12122]. However, recent studies demonstrated that the prevalence of postmicturition symptoms might be higher than that previously expected, and some studies reported that the prevalence was over 50% [523]. It might be necessary to consider postmicturition symptoms in patients with LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…Another study involving more than 7,000 men aged 30 to 80 years showed that the prevalence of PMD was 58.1% [5]. Another internet-based study involving 30,000 people from the general population reported an overall PMD prevalence of 46% [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in another postmicturition symptom, postmicturition dribble, a similar, approximately 6% increase in symptom prevalence was observed in both treatment groups. As postmicturition dribble is rather common also in younger men, a probable pathophysiological mechanism may be, instead of prostatic enlargement only, a failure of the bulbocavernous muscle to perform a normal postvoid milking reflex, with urine becoming trapped in the bulbar area of the urethra just after voiding . Surgical treatment could increase this ‘dead space’ distal from bladder neck and even exacerbate postmicturition dribble.…”
Section: Discussionmentioning
confidence: 99%